Pengaruh Gaya Kepemimpinan dan Kepuasan Kerja Terhadap Tingkat Loyalitas Karyawan - Zahra, Salsabila; Sutisna, Adang (Mansion: Management and Business on Kebangsaan, 2025)
Introduction: In service-based industries like wedding organizers, employee loyalty is a crucial factor that supports operational continuity and organizational reputation. This study examines how leadership style and job satisfaction influence employee loyalty at PT. Koloni Semut Pratama, a wedding organizer company based in Bandung. Background Problems: The main research problem revolves around the observed fluctuation in employee loyalty, possibly linked to leadership effectiveness and perceived job satisfaction. The central research question is: To what extent do leadership style and job satisfaction influence employee loyalty, both individually and collectively? Novelty: While numerous studies have explored similar variables in corporate settings, few have analyzed them within creative service companies like event organizers. This study fills that gap by focusing on a dynamic, client-facing industry with unique leadership and job satisfaction challenges. Research Methods: This quantitative study utilized a saturated sampling technique involving 45 employees. Data were collected through structured questionnaires and analyzed using multiple linear regression via SPSS 25, along with t-tests and F-tests to examine partial and simultaneous effects. Finding/Results: The findings show that both leadership style and job satisfaction significantly affect employee loyalty. Leadership style contributes 50.3% and job satisfaction 28.6% to the variance, with a combined effect of 78.9%. Conclusion: The study concludes that enhancing leadership effectiveness and improving job satisfaction are critical strategies to foster stronger employee loyalty in the event service industry. These findings provide practical insights for HR management in similar organizational contexts.